Palestinian Solidarity Action: The Dynamics of Politicized and Religious Identity Patterns Among Student Activists - Shadiqi, Muhammad Abdan; Muluk, Hamdi; Milla, Mirra Noor (UI Scholars Hub, 2018)
This study attempted to explain the factors that lead Muslim student activists to participate in Palestinian solidarity actions by testing the Social Identity Model Collective Action model (SIMCA, van Zomeren, Postmes, & Spears, 2008). A survey of 303 student members/administrators of Islamic organizations was conducted. The sample was obtained from more than seven Islamic-based student organizations. Collective solidarity actions were comprised of peaceful actions such as demonstrations, protests, and petition signings. The model involved two identities (politicized and religious) and two mediators (group efficacy and group-based anger). Results of the Structural Equation Modeling (SEM) analysis suggest that politicized identity, as indicated by strength of participants’ affiliations with Islamic movement organizations, predicts solidarity action intention more effectively than religious identity. Other study findings demonstrated that group efficacy is a significant partial mediator of the interaction between politicized and religious identities, and collective action. Religious identity has a stronger interaction with collective action than politicized identity within the partial mediating effect of group efficacy. Meanwhile group-based anger does not influence the desire to engage in collective action either directly or as a mediator.